(untitled) (Journal of Governance and Development (JGD), 2021)
This study examines the effect of board magnitude and board expertise of listed non-financial firms in Nigeria. The study population comprised all the 116 quoted non-financial companies in Nigeria. Eighty-nine (89) firms were selected, making 890 firm-year observations using the Taro Yamane sample selection method. Also, stratified and proportionate sampling techniques were employed. Generalized Least Square regressions were employed as a procedure for analyzing the data. The study established that board magnitude and board experts significantly affect the shareholder value of listed non-financial firms in Nigeria. The study concludes that characteristics of corporate governance that influence shareholder value are board magnitude and board expertise. Based on the findings and conclusion, the study suggested that the number of directors on the board should be increased to strengthen the monitoring mechanism of non-financial firms in Nigeria. Also, the management should increase the number of directors with accounting literacy on their board if they also seek to maximize shareholder value.